Decadent Culturemes. Translating Bernard Shaw’s Widowers’ Houses into Italian - Elisa Bizzotto (Lea, 2024)
This article discusses my recent Italian translation (2022) of George Bernard Shaw’s first play, Widowers’ Houses (1892), mainly by considering the concept of the cultureme. Culturemes, which are semantic units that exemplify and serve as paradigms of certain cultures, have been employed in translation studies in recent years to see how, and even if, culture-specific concepts can be translated. Culturemes are here seen in the light of the transculturality of decadent poetics, and hence interpreted as possible facilitators in the translation into Italian of Widowers’ Houses, a play written in the decadent period, and developing many features of decadent poetics, whose author utilised key transcultural concepts of the period. Viewing Shaw’s text from the perspective of such decadent culturemes as the slums, Cockney English and other decadent sociolects, and the decadent hero, together with the New Woman, not only substantiate the idea of Shaw as a decadent artist, but also suggest possible translation practices and processes for decadent literature.